Implementasi Knowledge Management dalam Mendukung Keberlanjutan Bisnis pada UMKM Wedding Organizer: Studi Kasus TENTANGKITA Wedding Organizer Kota Medan - Gusti, Muhammad Farhan; Rahmadani, Vivi Gusrini; Anizar, Anizar (Jurnal Ragam Pengabdian, 2026)
This study aims to analyze the implementation of knowledge management in TENTANGKITA Wedding Organizer, examine the role of organizational learning in transforming knowledge into organizational capabilities, and explore its contribution to business sustainability. A qualitative approach with a single case study design was employed. Data were collected through in-depth interviews, observations, and document analysis involving owners, employees, customers, and prospective customers. Data were analyzed using thematic analysis supported by NVivo 12. The findings reveal that knowledge management is implemented through four interconnected processes: knowledge capture, knowledge storage, knowledge sharing, and knowledge application. Organizational knowledge is primarily derived from project experiences, customer interactions, vendor relationships, and operational problem-solving activities. The study demonstrates that organizational learning serves as a key mechanism that transforms individual experiences into collective organizational capabilities. Through this process, knowledge management contributes to improved service quality, stronger organizational reputation, and enhanced organizational adaptability. Business sustainability is achieved through three dimensions: operational sustainability, reputational sustainability, and capability sustainability. The study proposes a thematic model showing that the relationship between knowledge management and business sustainability is mediated by organizational learning. These findings contribute to the knowledge management literature by providing empirical evidence from a project-based creative service SME context.